Strategi Mempertahankan Perekonomian Keluarga Usaha Mikro Kecil dan Menengah di Tengah Pandemi Covid-19 Desa Kurau Barat, Kecamatan Koba: STRATEGY OF MAINTENING THE ECONOMY OF SMALL AND MEDIUM MICRO BUSINESS FAMILY IN THE CENTRAL OF THE COVID-19 PANDEMIC, KURAU BARAT VILLAGE, KOBA DISTRICT - Hammidah Quranis; Putra Pratama Saputra; Fitri Ramdhani Harahap (Inovbook, 2022)
This study uses a descriptive type of research with a qualitative approach. The data sources of this research are primary data in the form of informants and secondary data in the form of documents and literature. The data analysis used is interactive analysis with three stages, namely data reduction, data modeling and drawing conclusions. The results showed that high trust between individuals can form strong social capital so that they are able to form social networks within a group. The social capital owned by the village of Kurau Barat with existing MSMEs is very much felt so that it provides effective results for the development of the businesses they manage. The role of social capital in each individual affects the capacity and quality within the village. Effective use of social capital can provide impetus for business development. Internal development of the